2018
DOI: 10.1016/j.ijmachtools.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

On the inverse design of discontinuous abrasive surface to lower friction-induced temperature in grinding: An example of engineered abrasive tools

Abstract: In order to lower temperature, abrasive tools with passive-grinding, e.g. textured, areas (PGA) have been suggested. However, most of the reported PGA geometries (e.g. slots, holes) have been determined based on the engineering intuition (i.e. trial and error) rather than in-depth phenomenological analysis. To fill this gap, this paper proposes a method to design the PGA geometry according to the desired temperature, i.e. the inverse design method. In the method, the analytical model of grinding temperature fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…As shown in Figure 2 a, a thermocouple was inserted into the narrow slot on the workpiece to measure the grinding temperature. This method was generally used to record temperature variation with good accuracy [ 14 , 15 ]. The thermocouple sensing tips were located close to the grinding surface, and the narrow slots were sealed with waterproof and heat-resistant glue, which could prevent the cooling liquid from affecting the measurement results.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
“…As shown in Figure 2 a, a thermocouple was inserted into the narrow slot on the workpiece to measure the grinding temperature. This method was generally used to record temperature variation with good accuracy [ 14 , 15 ]. The thermocouple sensing tips were located close to the grinding surface, and the narrow slots were sealed with waterproof and heat-resistant glue, which could prevent the cooling liquid from affecting the measurement results.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
“…The simulation and experimental results were compared, and it was concluded that different design parameters of the wheel affect the ground components at different rates.
Figure 18. Comparison of conventional, segmented and textured grinding wheels. 166
…”
Section: Advancements In Grindingmentioning
confidence: 99%
“…The results of theoretical and experimental studies of thermal processes during intermittent gear grinding should be considered as scientific prerequisites for solving this problem [1,2]. On their basis, practical recommendations were developed for determining the geometric characteristics of intermittent abrasive wheels and the parameters of grinding modes according to the temperature criterion [3,4]. Works [5,6] also provided practical recommendations for selecting the parameters of gear grinding modes under various processing conditions.…”
Section: Introductionmentioning
confidence: 99%